The Integration of Decarbonization and Resilience Strategies in Shaping Sustainable Cities - Mohammadpourlima, Naghmeh; Lü, Xiaoshu; Nygård, Mikael; Girgibo, Nebiyu (Springer, 2024)
In the face of escalating climate challenges, cities are taking the lead in adopting sustainable practices to mitigate carbon emissions and enhance their resilience to environmental issues. The transition towards decarbonization not only addresses the urgent need to mitigate climate change but also contributes to building resilient cities capable of adapting to a wide range of challenges. On the other hand, resilience ensures that decarbonization efforts endure and thrive, fostering long-term effectiveness and societal backing. This mutually reinforcing relationship between the two concepts highlights the importance of combining them for a holistic and integrated approach to building sustainable and climate-resilient urban environments. This article examines the relationship between decarbonization and resilience strategies, providing a comprehensive framework to illustrate their interaction to achieve sustainable and resilient cities. The methodology of the research contains three phases. The initial stage consists of carrying out a literature review to understand the concepts. Subsequently, the findings are integrated to develop a unified conceptual framework. The final phase illustrates how the collaboration between decarbonization, and resilience contributes to achieving sustainable cities. The article highlights the need for interconnected strategies to fortify cities against climate challenges while concurrently reducing their carbon emissions.
Keywords: Decarbonization; Sustainable Cities; resilience; fi=Energiatekniikka|en=Energy Technology|